Experimenal investigation on the use of secondary refrigerant in freezer for energy savings - Haryono, Aries Prih (2013)
This study presents an experimental study on a freezer which has small cooling capacity. Typically a freezer uses primary refrigerant (direct cooling) to cool or freeze a product. In this study, a prototype of freezer using a compressor 250 W nominal power at 220V was designed and constructed. The freezer is operated on two conditions, that is, using primary and secondary refrigerant. R22 and R290 (propane) were used as primary refrigerant, whereas aqueous solution of propylene glycol as secondary refrigerant. Comparison of the system performance between the primary and the secondary refrigerant werepresented. Also, the experimental results showed that the use of R290 as primary refrigerant to replace R22 in the freezer could save electrical power consumption by 18.5%. Meanwhile, the use of the secondary refrigerant yielded energy savings by 33.19% compared with the primary refrigerant.